Omicron: Subvariants, Flurona, Deltacron media misinformation and plot twists - Robinson, Jared; Banerjee, Indrajit (Journal of Advances in Internal Medicine, 2022)
The worldwide SARS-CoV-2 pandemic has taken the global community through a series of unprecedented events. The frustrating and crippling element in the global COVID saga is that of the catastrophic mutations and or discoveries which set the barely recovering fragile global markets and medical systems alight. One such mutation which ravaged the global recovery and crippled international trade and travel was the Omicron variant. Omicron and its subvariants are rising and becoming the predominant variants globally. The BA.2 subvariant however is seeing an increase in cases due to its enhanced transmissibility an secondary attack rate, it is however not of great concern as no vaccine efficacy discrepancy is evident between the predominant BA.1 variant subtype and that of BA.2. The global community is hypersensitive to COVID-19 and any new findings, it is therefore of the upmost importance that media outlets do not sensationalize and or misconstrue any new information, as such instances can have massive international repercussions. Flurona is not a hybrid virus and is simply a co-infection of the simple seasonal influenza and the Omicron variant, although this co-infection is highly serious, no risk of genetic recombination and hybrid formation is present. Finally, a recombinant variant of the Delta and Omicron variant has been discovered in the UK and is under investigation, initial reports however do not flag the variant as one of concern, more research and data will need to be assessed as for experts to ascertain whether it is a cause for additional health measures or not.